Portas do Mar and Doca da Marinha, Lisbon. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
Campo das Cebolas – or Ribeira Velha – was, in its origin and for centuries, a fairground connected to the port. However, at the time of the international competition launched in the context of the 13th Venice Architecture Biennale, it was a place where cars were parked disorderly. The proposed project was based on the intention of making this space once again unobstructed and available to people. A new square was therefore created, gathered under a tree cover, with a slight slope to-wards the Saramago Foundation and its new bookshop. The slope that raises the car park and the square creates a gradient in relation to the waterfront which, associated with a low height wall, allows the acoustic insulation of the square.